The Mini-TRH Test, Dopamine Transmission, and Schizophrenia Symptoms - Johan Spoov (BioChem)
Studies in animals and humans suggested that the tonic dopamine inhibition of prolactin release may be estimated by submaximal prolactin stimulation by thyrotropin-releasing hormone (TRH), the mini-TRH test. Because patients with schizophrenia may be more vulnerable to stress-induced elevations of prolactin, great care was taken to avoid stress-induced increases in prolactin, including applying local anaesthesia before blood extraction in our psychotic patients. Basal prolactin levels were in the reference range in all psychotic patients studied by us and were not higher in male patients than in normal men. Results of the mini-TRH test suggested that in acute patients with non-affective psychoses, everyday memory problems, non-paranoid delusions, and first-rank symptoms, but not other Comprehensive Psychopathological Rating Scale (CPRS) positive symptoms, could correlate with decreasing dopamine transmission in lactotrophs. In acute patients with first-episode schizophrenia, increasing negative disorganisation symptoms might correlate with increasing dopamine transmission. In first-episode patients, a hypersensitivity of the TRH response was detected, which could indicate that variability in the basal prolactin levels may confound the interpretation of the mini-TRH response. To avoid that, a smaller dose of TRH was recommended in first-episode patients. Studies using other estimates of basal dopamine release suggested that striatal dopamine transmission reflected delusions and hallucinations but not other Positive and Negative Symptom Scale (PANSS) positive symptoms. Including a wide range of symptoms in the PANSS positive scale may reduce its specificity for assessing basal dopamine transmission, although the scale remains useful for tracking treatment response.